CURRENT RATIO, EARNING PER SHARE AND DEBT TO EQUITY RATIO AFFECTS STOCK RETURNS - Widianti, Widianti; Apriyanti, Metha Dwi (Univesitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to determine the effect of the current ratio, earning per share and debt to equity ratio on stock returns in property and real estate sub sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2016-2020 period. The population of this study includes all property and real estate sub sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used was purposive sampling technique. Based on the predetermined criteria obtained 11 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is multiple linier regression analysis supported by SPSS V.25 program. The results show that the current ratio, earning per share and debt to equity ratio have an influence on stock returns.Keywords: Current Ratio, Earning Per Share, Debt to Equity Ratio, Stock Returns.